Nomogram based on clinical and brain computed tomography characteristics for predicting more than 5 cerebral microbleeds in the hypertensive population - Wang, Xin-Bin; Dong, Hao; Qiu, Yong-Gang; Lou, Cun-Cheng; Huang, De-Yun; Zhang, Jing; Chen, Di-Hong; Feng, Han; Fang, Xu (Frontiers in Neurology, 2022)
Background: Cerebral microbleeds (CMBs) are common in the hypertensive population and can only be detected with MRI. The anticoagulation and thrombolytic regimens for patients with >5CMBs are different from those for patients with ≤5CMBs. However, MRI is not suitable for evaluating CMBs in patients with MRI contraindications or acute ischaemic stroke urgently requiring thrombolysis. We aimed to develop and validate a nomogram combining clinical and brain CT characteristics for predicting >5CMBs in a hypertensive population. Materials and Methods: In total, 160 hypertensive patients from 2016 to 2020 who were confirmed by MRI to have >5 (77 patients) and ≤5CMBs (83) were retrospectively analysed as the training cohort. 64 hypertensive patients from January 2021 to February 2022 were included as the validation cohort. Multivariate logistic regression was used to evaluate >5CMBs. A combined nomogram was constructed based on the results, while clinical and CT models were established according to the corresponding characteristics. Receiver operating characteristic (ROC) and calibration curves and decision curve analysis (DCA) were used to verify the models. Results: In the multivariable analysis, the duration of hypertension, level of homocysteine, number of lacunar infarcts (LIs) and leukoaraiosis (LA) score were included as factors associated with >5CMBs. The clinical model consisted of the duration of hypertension and level of homocysteine, while the CT model consisted of the number of LIs and LA. The combined model consisted of the duration of hypertension, level of homocysteine, LI and LA. The combined model achieved an area under the curve (AUC) of 0.915 (95% CI: 0.860-0.953) with the training cohort and 0.887 (95% CI: 0.783-0.953) with the validation cohort, which were higher than those of the clinical model (training cohort: AUC, 0.797 [95% CI: 0.726, 0.857]; validation cohort: AUC, 0.812 [95% CI: 0.695, 0.899]) and CT model (training cohort: AUC, 0.884 [95% CI: 0.824, 0.929]; validation cohort: AUC, 0.868 [95% CI: 0.760, 0.940]). DCA showed that the clinical value of the combined model was superior to that of the clinical model and CT model. Conclusion: A combined model based on clinical and CT characteristics showed good diagnostic performance for predicting >5CMBs in hypertensive patients.